CsSn0.5Pb0.5Br3@CS-FA Nanoparticles as a Fluorescent Tracer for the Preliminary Diagnosis of Leptomeningeal Carcinomatosis - Jian Li; Yu Zhang; Rongrong Yan; Siyu Chen; Ruohao Li; Yinan Jiao; Hui Bu (Discovery Medicine, 2026)
Background: Leptomeningeal carcinomatosis (LC) remains difficult to diagnose at an early stage because current diagnostic approaches rely primarily on magnetic resonance imaging and cerebrospinal fluid (CSF) cytology, which may lack sensitivity or require repeated testing. This study aimed to develop a water-stable, biocompatible, and tumor-targeted fluorescent nanoparticle for the preliminary diagnosis of LC.Methods: CsSn0.5Pb0.5Br3@CS-FA nanoparticles were synthesized using a water-triggered strategy and characterized by X-ray diffraction, Fourier-transform infrared spectroscopy, transmission electron microscopy, photoluminescence spectroscopy, ultraviolet-visible spectroscopy, and in vivo imaging. Their water stability, in vitro targeting ability, cytocompatibility, in vivo tumor-targeting capacity, and biosafety were evaluated using Lewis lung carcinoma (LLC) cells, C2C12 cells, C57BL/6JNifdc mouse models, and clinical CSF samples. CSF samples from 7 patients with LC and 7 non-LC controls were incubated with the nanoparticles, and fluorescence intensity was detected by flow cytometry.Results: CsSn0.5Pb0.5Br3@CS-FA nanoparticles showed a stable core-shell structure and maintained fluorescence in aqueous solution for up to 329 days. In vitro imaging demonstrated stronger fluorescence in LLC cells than in C2C12 cells, and CsSn0.5Pb0.5Br3@CS-FA produced significantly higher fluorescence than non-targeted CsSn0.5Pb0.5Br3@CS nanoparticles (p < 0.001). Cell viability remained above 90% after treatment with 200 μg/mL CsSn0.5Pb0.5Br3@CS-FA. In tumor-bearing mice, fluorescence signals were detectable after injection, peaked at 24 h, and were no longer detectable at 216 h. Hematological, hepatic, renal, histological, and body-weight assessments showed no obvious biosafety concerns. In clinical CSF samples, the fluorescence intensity was markedly higher in the LC group than in the non-LC group (47.08% ± 13.56% vs. 2.75% ± 1.12%, p < 0.001).Conclusion: CsSn0.5Pb0.5Br3@CS-FA nanoparticles exhibited favorable water stability, tumor-targeting ability, fluorescence performance, and preliminary biosafety. Their enhanced fluorescence signal in LC-derived CSF samples suggests potential value as an auxiliary fluorescent tracer for LC diagnosis, although further validation in larger clinical studies is required.